The consequences of EU enlargement for Central and Eastern labour markets - Michael Christopher Burda (EIB Papers, 1998)
Two or three decades from now, economic historians will note that a hallmark of successful transformation in Central and Eastern Europe (CEE) was the speed in which it became a non-issue for the body politic. A corollary of this is the expectation that, as formerly centrally planned economies irrevocably transfer responsibility for resource allocation to markets, they will increasingly resemble and behave little differently from other less-developed OECD countries or advanced developing economies. The prospect of accession to the European Union has heightened an already exaggerated optimism that this transition will take little or no time at all. Since 1993, GDP in Poland has grown by more than 30 percent; in the Czech Republic by eleven percent; in Hungary by nine percent; and in Slovakia by more than 20 percent. But there is much work left to be done; these countries remain at per capita income levels well below those of the poorest EU members (1).
Keywords: 330; Arbeitsmarktpolitik; EU-Erweiterung; Osteuropa; Ostmitteleuropa